2002
DOI: 10.1089/10445460252943542
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence Between Adolescent Report, Parent Report, and Teacher Report of Manic Symptoms

Abstract: Manic symptoms are relatively nonspecific in outpatient samples. Using more than one informant increases the likelihood of selecting subjects with serious and possibly manic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…In addition, despite the fact that the correlations between informants are significant, they are moderate in size, as is typical in the child and adolescent outcome literature (e.g. Foley et al, 2004;Grietens et al, 2004;Grills & Ollendick, 2003;Loeber, Green, Lahey, & Kalb, 2000;McConaughy, 1993;Thuppal, Carlson, Sprafkin, & Gadow, 2002). If such is the case, Achenbach et al (1987) advocate the use of outcome data from multiple informants and recommend that ratings not be substituted for each other.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, despite the fact that the correlations between informants are significant, they are moderate in size, as is typical in the child and adolescent outcome literature (e.g. Foley et al, 2004;Grietens et al, 2004;Grills & Ollendick, 2003;Loeber, Green, Lahey, & Kalb, 2000;McConaughy, 1993;Thuppal, Carlson, Sprafkin, & Gadow, 2002). If such is the case, Achenbach et al (1987) advocate the use of outcome data from multiple informants and recommend that ratings not be substituted for each other.…”
Section: Discussionmentioning
confidence: 99%
“…In other research, sometimes convergence between reports points to greater impairment and/or poorer outcomes, and sometimes not (cf. Carlson and Youngstrom 2003;Fergusson et al 2009;Thuppal et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have found, however, that the results from multiple informants often provide contradictory information that is, at best, difficult to interpret and, at worst, not useful in guiding diagnosis and treatment (Achenbach et al, 1987;Ruffalo & Elliott, 1997). The reason most cited for the discrepant perceptions is that child behavior may be situationally specific (Achenbach et al, 1987;McKim & Cowen, 1987;Ruffalo & Elliott, 1997;Thuppal, Carlson, Sprafkin, & Gadow, 2002). For example, teachers might see behaviors at school that parents do not see at home, or vice versa.…”
mentioning
confidence: 99%
“…Although some researchers (Thuppal et al, 2002) have found it useful to incorporate teacher report of child and adolescent behavior to maximize diagnostic certainty (similar to findings with attention deficit hyperactivity disorder [ ADHD]) (Vaughn, Riccio, Hynd, & Hall, 1997), other data have suggested that teacher report is markedly less valuable than parent report when identifying BPSDs in this population (Geller, Warner, Williams, & Zimerman, 1998;Hazell, Lewin, & Carr, 1999;. In general, large discrepancies between parent, teacher, and youth ratings of behavior problems in pediatric BPSDs have been reported across a number of studies (Hazell et al, 1999;Kahana, Youngstrom, Findling, & Calabrese, 2003;.…”
mentioning
confidence: 99%